Analysis of the mechanical transfer characterization between lodged sugarcane and the cutter by simulation modeling with UMAT subroutine - Liu, Tao; Wang, Qingqing; He, Jiaxun; Xie, Dongbo; Liu, Zhipeng; Liu, Lichao; Chen, Liping (International Journal of Agricultural and Biological Engineering, 2024)
Cutting the roots of sugarcane using cutters is a critical part of sugarcane harvesting, and the degree of breakage of the roots after cutting affects the germination and growth of sugarcane to a certain extent in the following year. However, the intricate interactions between the cutter and the stalk remain unclear. In order to fill this gap, this study first analyzed the conditions for no missed cuts during the operation of a double-disk cutter. Secondly, the research established a model of sugarcane stalk with anisotropy using the User-defined Material Mechanical Behavior (UMAT) subroutine based on the secondary development module of ABAQUS/Explicit. The cutting force curves obtained from simulation and test show a high correlation coefficient (R2=0.9621), indicating the reliability of the model of sugarcane stalk in mechanical transfer. Subsequently, the simulation test of the blade rotating cutting characteristics in this study indicates that at a blade tilt angle of 11.3°, a blade rotating speed of 659.3 r/min, and a forward speed of 1.5 km/h, the maximum shear force on the blade is the largest, while the maximum cutting force is the smallest. Finally, based on the simulation results, this paper discussed the internal factors affecting the breakage rate of sugarcane stalks and predicted the damage location and damage force of the stalks by studying the stress wave transmission effect. Additionally, it analyzed the effects of single-knife cutting and multi-cutting on stalk incisions. The results indicated that multi-cutting causes more damage to the stalks and increases the breakage rate of sugarcane. The results of this study can provide a theoretical basis and technical reference for exploring the reduction of sugarcane residual cutting rate. Keywords: sugarcane harvesting, UMAT, mechanical transfer characterization, cutter, simulation modeling DOI: 10.25165/j.ijabe.20241703.8880 Citation: Liu T, Wang Q Q, He J X, Xie D B, Liu Z P, Liu L C, et al. Analysis of the mechanical transfer characterization between lodged sugarcane and the cutter by simulation modeling with UMAT subroutine. Int J Agric & Biol Eng, 2024; 17(3): 39-49.